Antecedents And Consequences of Organizational Learning Climates: A Meta-Analysis Using Maslow’s Hierarchy of Needs Theory - Vithayaporn, Sanhakot; Katekaew, Rungkaew; Vorapanya, Chantarat; Sanpetpanich, Sutha (ABAC ODI JOURNAL Vision. Action. Outcome, 2022)
The purpose of this paper is to determine the antecedents and consequences of “organizational learning climates”, which are the co-creation of an organization and employees. It presents the diverse definitions of organizational learning climates from various studies. Four main elements/factors that impact an organizational learning climate include the physical, psychological, social, and technological learning climates that influence employees to participate in any learning activity (Gregory, 2016). Maslow’s hierarchy of needs theory was used to explain the elements/factors of learning climates according to the basic needs of humans. This conceptual paper used a literature review, document analysis, and meta-analysis methods to examine organizational learning climates. The primary 100 articles were initially analyzed and extracted to a final 50 articles using categorization criteria to synthesize the results. The study found that the four main elements of learning climates are aligned with Maslow’s theory's hierarchy of needs: physical needs, security and safety, love and belonging, self-esteem, and self-actualization, which are integrated with the physical, psychological, social, and technological learning climates that impact individuals’ willingness to learn, and organizations’ emphasis on encouraging employees’ learning. The discussion and conclusions also present how organizational learning climates make a transitional leap to a learning organization. The limitations and recommendations are involved with the fact that the empirical studies of learning climates in a business management context are limited. Thus, it is recommended that future research should be based on a large organization, to identify the strategic activities that may cause the transition to a learning organization